(untitled) (Journal of Atomic and Molecular Sciences, 2010)
We investigate the thermodynamic properties of the potential superhard orthorhombic structure boron-carbonitride β-BC_2N by using ab initio plane-wave pseudopotential density functional theory method within both local density approximation (LDA) and generalized gradient approximation (GGA). The lattice parameters (a, b and c), equilibrium volume V, bulk modulus B_0 and its pressure derivative B_0' have been calculated, and compared with those of diamond and cubic boron nitride (c-BN). The obtained results are in excellent agreement with the available experimental data and other theoretical results. Through the quasi-harmonic Debye model, we also investigate the thermodynamic properties of β-BC_2N. The variation of the thermal expansion α, the heat capacity C_V and the Grüneisen parameter γ with pressure P and temperature T, as well as the pressure-normalized volume (P-V_n) and the pressure- bulk modulus (P-B) relationship of β-BC_2N are obtained systematically.